Metodologi Penentuan Arah Kiblat Menggunakan Google Earth: Pendekatan Saintifik Dalam Kajian Fikih Ibadah - Machzumy, Machzumy (PT. Student Rihlah Indonesia, 2026)
Determining the direction of the Qiblah is one of the valid conditions for performing Islamic prayer (salat), with strong normative foundations in the Qur'an and Hadith. The advancement of geospatial technology, particularly Google Earth, opens new horizons in Qiblah determination methodology that is more accessible to the general public. This study aims to: (1) comprehensively analyze the methodological procedure for determining the Qiblah direction using Google Earth; (2) examine its scientific validity through comparison with the Vincenty Formula as the international geodetic standard; and (3) elaborate a contemporary jurisprudential (fiqh) framework on the use of digital technology in the context of Islamic worship. A qualitative-comparative method was employed with extensive library research and field observation at 20 representative locations across Indonesia. Results indicate that Google Earth, when used with proper procedures, achieves Qiblah determination accuracy with an average deviation of ±0.32 degrees from Vincenty Formula calculations, surpassing the tolerance threshold established by national astronomical standards. The fiqh analysis concludes that the use of Google Earth falls within the category of ijtihad bi al-'ilm and aligns with maqashid al-shari'ah in facilitating higher-quality worship. This research recommends the development of national standard protocols for geospatial technology use in Qiblah determination.